Techno-economic analysis of the transition toward the energy self-sufficiency community based on virtual power plant - Wang, Yafei; Gao, Weijun; Li, You; Qian, Fanyue; Yao, Wanxiang (Frontiers in Energy Research, 2023)
Distributed energy resources are important measures to increase energy self-sufficiency and overcome the global carbon reduction problem. However, individual planned renewable energy generation poses a significant threat to the power grid. Therefore, virtual power plant (VPP) is attracting considerable attention as a means of aggregating distributed energy in urban areas. This study proposed a VPP model consisting of updating high-efficiency appliances and photovoltaic and energy storage systems. A comprehensive analysis for assessing the technical, economic, and environmental benefits derived from the VPP was presented, indicating the feasibility of a smart community to achieve power self-sufficiency with the support of the VPP. A smart community in Japan was selected as the research object, with a peak power demand of 57,350 kW. The VPP’s load leveling performance, return on investment (ROI), and CO2 emission reduction were analyzed. In addition, external factors, such as electricity price changes and FiT policies, are considered to assess the impact on the economics of the VPP. The results show that the introduction of the VPP system in the community can effectively stabilize the grid load with a peak shaving rate reaching 42.55% and improve the energy self-sufficiency rate of the region reached 100%, besides providing superior economic and environmental benefits (16.26% CO2 emission reduction) on the demand side. Furthermore, the economic performance of VPP shows a good prospect with the fall in equipment prices and the future trend of carbon tax growth. This study provides important insights into the development of VPP in other countries, especially for low-energy self-sufficiency regions.